Defer no more: advances in the treatment and prevention of chronic hepatitis C virus infection in children. Issue 5 (15th October 2022) - Honegger, Jonathan R.; Gowda, Charitha
Abstract : Purpose of review: Direct-acting antiviral (DAA) regimens targeting hepatitis C virus (HCV) are now approved for young children. This review examines recent DAA experience in children, current treatment recommendations and challenges, and potential treatment-as-prevention strategies. Recent findings: In 2021, the US FDA extended approval of two pan-genotypic DAA regimens, glecaprevir/pibrentasvir and sofosbuvir/velpatasvir, to children as young as age 3 years based on high success rates and reassuring safety profiles in registry trials. Similar performance has been replicated with real-world DAA use in thousands of adolescents and in limited reports of children with high-risk conditions, including cirrhosis, cancer, thalassemia and HIV-coinfection. Treatment without delay is now recommended in the USA for viremic children aged 3 years and up to prevent disease progression and future spread. To date, treatment expansion is limited by high rates of undiagnosed paediatric infection. Universal prenatal screening will aid identification of perinatally exposed newborns, but new strategies are needed to boost testing of exposed infants and at-risk adolescents. Postpartum treatment programmes can prevent subsequent vertical transmission but are hampered by low rates of linkage to care and treatment completion. These challenges may be avoided by DAA use in pregnancy, and this warrants continued study. Summary: Paediatric HCV is now readily curable. Substantial clinical and public health effort is required to ensure widespread uptake of this therapeutic breakthrough.